100 years of X-ray crystallography. (1st March 2017) - Kemp, Terence; Alcock, Nathaniel
The developments in crystallography, since it was first covered in Science Progress in 1917, following the formulation of the Bragg equation, are described. The advances in instrumentation and data analysis, coupled with the application of computational methods to data analysis, have enabled the solution of molecular structures from the simplest binary systems to the most complex of biological structures. These developments are shown to have had major impacts in the development of chemical bonding theory and in offering an increasing understanding of enzyme–substrate interactions. The advent of synchrotron radiation sources has opened a new chapter in this multi-disciplinary field of science.